The burden of periprosthetic joint infections: patient-reported outcomes and qualitative insights into periprosthetic joint infections - Dally, Franz Joseph; Kixmöller, Frido; Bludau, Frederic; Gravius, Sascha; Darwich, Ali; Betsch, Marcel (Journal of Bone and Joint Infection, 2025)
Introduction: Periprosthetic joint infections (PJIs) have a severe physical impact and impose a significant psychological burden. This study aimed to compare patient-reported outcome measures (PROMs) and qualitative interview data within the same study cohort. Methods: A total of 28 PJI patients were identified after completing treatment for hip or knee PJIs. Qualitative interviews were conducted, and PROMs - such as the hip disability and osteoarthritis outcome score (HOOS), knee injury and osteoarthritis outcome score (KOOS), hospital anxiety and depression scale - total (HADS-T) score, and brief pain inventory (BPI) score - were assessed. The data were then evaluated for correlations between the PROMs and the qualitative interview findings. Results: A total of 20 out of 28 (71.4 %) patients scored above the accepted threshold of ≥10 on the HADS-T. A total of 8 out of 28 (28.6 %) patients scored low on the HADS-T. Through semi-structured interviews, we further evaluated the two groups: a high-HADS-T-scoring group and a low-HADS-T-scoring group. PJI patients scoring high on the HADS-T experienced a heavier psychological burden than those scoring low on the HADS-T. Our qualitative data show that the high-HADS-T-scoring group perceived their PJI experience as troubling and psychologically distressing; moreover patients in the high-HADS-T-scoring group did not deal with the PJI as well as those in the low-HADS-T-scoring group. Conclusions: This study provides valuable information regarding the screening of PJI patients who are at risk of psychological disorders using the HADS-T. Following screening, it also provides insight into which patients should be closely monitored and which patients should be offered professional psychological support, as the latter resource is limited and needs to be distributed sensibly. PJI patients scoring above ≥10 on the HADS-T are high-risk patients and should be offered professional psychological support.
CRIS-Team Scopus Importer:2025-12-05